2016
DOI: 10.1039/c6nr04461a
|View full text |Cite
|
Sign up to set email alerts
|

Selenium nanoparticles incorporated into titania nanotubes inhibit bacterial growth and macrophage proliferation

Abstract: Since implants often fail due to infection and uncontrolled inflammatory responses, we designed an in vitro study to investigate the antibacterial and anti-inflammatory properties of titanium dioxide nanotubes (TNTs) incorporated with selenium nanoparticles (SeNPs). Selenium incorporation was achieved by the reaction of sodium selenite (Na2SeO3) with glutathione (GSH) under a vacuum in the presence of TNTs. Two types of bacteria and macrophages were cultured on the samples to determine their respective antibac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 44 publications
2
48
1
Order By: Relevance
“…Conversely, SeNPs were ineffective against both E. coli species. Reports in the literature have contrary effects of SeNP on E. coli; some researchers found antibacterial efficacy 6,32,33 while others did not. 29,34,35 At this moment, there is no conclusive mechanism for the bactericidal activity of SeNPs.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Conversely, SeNPs were ineffective against both E. coli species. Reports in the literature have contrary effects of SeNP on E. coli; some researchers found antibacterial efficacy 6,32,33 while others did not. 29,34,35 At this moment, there is no conclusive mechanism for the bactericidal activity of SeNPs.…”
Section: Discussionmentioning
confidence: 95%
“…Liu et al found that SeNP loaded into an anodized titanium nanotube repelled E. coli growth and identified three modes of action: membrane disruption, damage to adhesion-mediating proteins, and reactive oxygen species (ROS) generation. 6 However, Zonaro found that the amount of ROS generated by SeNPs (221.1-345.2 nm) did not correlate with the bacterial inhibition. 32 In addition, prior studies with SeNP-treated Staphylococcus epidermidis, a Gram-positive bacterium (submitted work) did not show damaged bacterial membranes, suggesting membrane disruption was not the primary mode of antibacterial activity and may account for why the SeNPs were ineffective against E. coli in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aureus, and S . epidermidis , and protect against bacterium‐mediated tissue injury . Concurrently, as macrophages highly express mannose receptors, mannose‐decorated nanoparticles can serve as excellent carriers delivering drugs into macrophages .…”
Section: Methodsmentioning
confidence: 99%
“…Hydrothermal reaction method was applied for the production of Se-doped TiO2 nanoparticles, according to Zavala et al [16] and Liu et al [17].Briefly, 7 g of TiO2 power (Sigma-Aldrich, CAS No-13463-76-7) was dissolved in 70 mL NaOH10N, by continuously stirring at 30°C, for 2 hours. The solution was introduced in autoclave at 1400 ͦ C for 24 hours.…”
Section: Experimental Part Preparation Of Se-doped Ti Nanoparticlesmentioning
confidence: 99%